Educación ambiental para la conservación del tiburón martillo (Sphyrna lewini) en el sitio Puerto Cabuyal, del cantón San Vicente - Castro Alcívar, Kevin Xavier (2021)
The objective of this research is to develop environmental education for the conservation of the hammerhead shark (Sphyrna lewini) in the Puerto Cabuyal site in San Vicente canton, Manabí province. The bibliographic, descriptive method and techniques such as interviews, surveys for the collection of information, as well as a design of environmental education strategies were used. As a result of the research, it was worked with 56 fishermen and 20 students, where around 70% have knowledge about the conservation of the hammerhead shark. With the information obtained in the initial diagnosis, the application of pedagogical tools of environmental education was carried out to strengthen capacities with workshops, educational talks and theater plays, where the latter had the highest index of motivation, attention and response capacity in the students with 100% satisfaction, followed by the community cinema, while the talk had a 72% in the motivation index and an 89% in the response capacity of the participants. The incidence of the applied strategy for the knowledge and perception of the participants was evaluated with a stratified random general survey, where it was determined that the activities carried out generated notion in the learning about the conservation and preservation of the hammerhead shark, concluding that the application of these strategies promoted the motivation of more than 74% of the participants to continue participating in training sessions for the conservation of hammerhead sharks in this community.